Multilineage Lymphoblastic Lymphoma as an Initial Presentation of Mixed Phenotype Acute Leukemia - Mako Ikeda; Wataru Nakahara; Mizuki Asako; Yuka Umeki; Yoshiki Matsuoka; Takuya Terakawa; Hitomi Matsunaga; Yuki Iwasa; Riko Saito; Yuki Iwama; Takahiro Matsui; Kazumasa Oka; et al. (Case Reports in Hematology)
Mixed phenotype acute leukemia (MPAL) is characterized by leukemic blasts that express markers of multiple lineages. Compared with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL), MPAL is considered to have a poor treatment outcome. We report a case of MPAL T/myeloid not otherwise specified that was initially presented as multilineage lymphoblastic lymphoma and subsequently developed into leukemic MPAL. An acute lymphoblastic leukemia-based treatment regimen was ineffective, but azacitidine and venetoclax therapy resulted in hematological complete remission. Our case suggests that multilineage lymphoblastic lymphoma should be considered to be the same disease as MPAL, albeit with different clinical presentations. Optimal treatment for MPAL has not been established yet, but azacitidine and venetoclax therapy may be a potential approach.